Creation and humanity: Veli‐Matti Kärkäinen's answer to the ultimate question. Issue 4 (28th August 2020) - Tóth, Viktor J.
Abstract: This article focuses on the third volume of Vel‐Matti Kärkkäinen's systematic theology, titled Creation and Humanity . After a brief overview of the volume the article offers some clarification on the tenth chapter, especially on its interaction with paleontology. After that, two constructive observations follow. The first is related to Kärkkäinen's notion of the embeddedness of human nature, and the second is to further employ systems thinking in his constructive work on creation and human evolution.